Modern contraceptive utilization and its associated factors among married women in Senegal: a multilevel analysis - Zegeye, Betregiorgis; Ahinkorah, Bright O; Idriss-Wheeler, Dina; Olorunsaiye, Comfort Z; Adjei, Nicholas K; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Utilization of modern contraceptives is still low in low-and middle-income countries, although fertility and population growth rates are high. In Senegal, modern contraceptive utilization is low, with few studies focusing on its associated factors. This study examined modern contraceptive use and its associated factors among married women in Senegal. Methods Data from the 2017 Continuous Demographic and Health Survey (C-DHS) on 11,394 married women was analysed. We examined the associations between the demographic and socioeconomic characteristics of women and their partners and modern contraceptive use using multilevel logistic regression models. Adjusted odds ratios with 95% confidence intervals (CI) were estimated. Results The utilization of modern contraceptives among married women was 26.3%. Individual level factors associated with modern contraceptive use were women’s age (45–49 years-aOR = 0.44, 0.30–0.63), women’s educational level (higher-aOR = 1.88, 1.28–2.76) husband’s educational level (higher-aOR = 1.43, 1.10–1.85)), number of living children (5 or more children-aOR = 33.14, 19.20–57.22), ideal number of children (2 children-aOR = 1.95, 1.13–3.35), desire to have more children (wants no more-aOR = 2.46, 2.06–2.94), ethnicity (Diola-aOR = 0.70, 0.50–0.99), media exposure (yes-aOR = 1.44, 1.16–1.79)), wealth index (richer-aOR = 1.31, 1.03–1.67) and decision making power of women (decision making two-aOR = 1.20, 1.02–1.41). Whereas, region (Matam-aOR = 0.35, 0.23–0.53), place of residence (rural-aOR = 0.76, 0.63–0.93), community literacy level (high-aOR = 1.31, 1.01–1.71) and community knowledge level of modern contraceptives (high-aOR = 1.37, 1.13–1.67) were found as significant community level factors. Conclusions The findings indicate that both individual and community level factors are significantly associated with modern contraceptive use among married women in Senegal. Interventions should focus on enhancing literacy levels of women, their husbands and communities. Furthermore, strengthening awareness and attitude towards family planning should be given priority, especially in rural areas and regions with low resources.